Madiun City Central Corridor Walkability Assessment Seen from Urban Structure - Saadhati, Nuzula Firda; Utomo, Rizon Pamardhi; Permana, Chrisna Trie Hadi (CV. Rayyan Dwi Bharata, 2024)
Walkability is the condition and quality of the pedestrian environment that is assessed through measuring the friendliness of the built environment and meeting the needs of pedestrians. In supporting the walkability of the area, it is not only done by beautifying the pedestrian path through the addition of physical accessories, but must be able to fulfill the aspects of usability, safety, accessibility, comfort, and a good environment. In this case, urban structure shows an important and significant factor because it can affect the ease of a person in moving places in urban areas, especially on foot. Urban structure components that affect walkability include land use diversity and road network configuration, which consists of connectivity and integration of the road network. The assessment of land use diversity is done through a derivative of the entropy index, namely weighted land use mixed (WLUM), while the road network configuration is assessed through space syntax. As a result, the Madiun City center corridor has a walkability value in the medium category. This shows that the urban structure in the central corridor of Madiun City is still not able to support the walking activities of its residents well, but also does not make it difficult for residents to carry out mobility on foot.